The tangibility of the intangibles: What drives banks' sustainability disclosure in the emerging economies? - Adam Ng (University of Oxford, Global Economic Governance Programme (GEG), 2016)
This article sheds light onto the tangibility of the intangibles, arguing that environment, social and governance sustainability ("ESG"), typically considered as intangibles, can be explained by tangible factors such as banks' fundamentals, country ESG performance, macroeconomic factors and institutional quality. Based on panel estimation of 251 banks from 45 emerging countries over the period 2005-2014, we find that size, liquidity, years of establishment and market power positively influence banks' disclosure of ESG policies and practices. Nonprofitable banks disclose ESG, probably to build reputation and to attract more customers. At the macro level, country ESG scores are positively correlated with environment and socialdisclosure, but do not have a significant effect on any governance indicators. While banks in countries with higher economic freedom tend to focus on and value the importance of ESG, this is not the case with banks in countries with more economic growth and financial openness. We also find that a financial crisis can reduce the probability of banks' disclosure. In the overall analysis, our models can explain the disclosure of environmental and social indicators better than governance indicators.
Keywords: 330; Sustainability; ESG Disclosure; Banks; Emerging Markets; Institutional Quality